Wear and impact analysis of granular materials using Discrete Element Method simulations - JAMES THOMPSON (2023)
Wear models for abrasion, ductile erosion, brittle erosion and combined erosion are implemented into a Discrete Element Method program utilising the linear spring dashpot model. A linear damage model is developed, implemented and then applied to an industrial case study through which it is found to predict wear accurately and provide a good insight into the improvement based on material change using the abrasion models. Four methods of creating energy based modelling were created for specific use inside DEM and contrasted with known wear models to assess what mechanisms they may potentially replicate. Through use with DEM, this allows use with a Single Element Failure criteria which can rapidly assess a variety of material changes inside a system to take steps to de-risk potential industrial trials. Design changes were made to assess the effects on both wear/energy models and provide predictions for causes and possible side effects. The effect of particle kinetics were assessed with respect to angle of impact, mass flow rate and coefficient of restitution to determine how this impacts wear modelling in DEM.